Redox status of biomarkers in serum of dogs with hypothyroidism and its treatment with levothyroxine sodium - Zhu, Ling; Han, Jinge; Bahetijiang, Halihaxi; Liu, Gang; Kastelic, John P.; Zhou, Xueying; Han, Bo (Frontiers in Veterinary Science, 2025)
Information regarding canine hypothyroidism in China remains limited, particularly regarding the redox status of affected dogs. Therefore, the objective of this study was to evaluate the redox status of dogs with hypothyroidism and observe how it changed after levothyroxine replacement therapy. A total of 10 healthy dogs (control group) and 10 dogs with hypothyroidism (treatment group) from China Agricultural University Veterinary Teaching Hospital were included in the study. The redox status was assessed in all 20 dogs. Thyroid profiles such as thyroxine (T4), free thyroxine (fT4), and thyroid-stimulating hormone (TSH) and biomarkers of oxidative stress, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-px), and malondialdehyde (MDA), were assessed on day 0 in all dogs and on days 14 and 45 post-levothyroxine sodium treatment in dogs with hypothyroidism. Dogs with hypothyroidism had decreased levels of serum T4 and fT4 and increased levels of serum TSH. Based on SOD, CAT, GSH-px, and MDA, dogs with hypothyroidism had oxidative stress. Following 45-day treatment with levothyroxine sodium (0.02 mg/kg orally twice daily), antioxidant parameters improved progressively: SOD increased from 60.2 to 76.7 U/mL (Day 0-14) and further to 83.3 U/mL (Day 45); CAT from 105.9 to 115.5 mU/mL (Day 0-14) reaching 132.9 mU/mL (Day 45); GSH-Px from 10.2 to 8.4 U/mL (Day 0-14) then 9.7 U/mL (Day 45), while MDA decreased from 8.2→6.8→4.4 μmol/L correspondingly. In conclusion, increased serum TSH and MDA concentrations, in addition to decreased serum T4 and fT4 concentrations and decreased SOD and CAT activities, indicated that there was oxidative stress in dogs with hypothyroidism. However, there were significant improvements in the redox status of biomarkers in the serum of dogs with hypothyroidism after treatment with levothyroxine sodium (0.02 mg/kg twice daily) for 45 days.